Theoretical estimation of efficiency defect in cascade refrigeration system using low global warming potential refrigerant pair. (2022) - Soni, Shubham; Mishra, Punit; Maheshwari, Govind; Verma, Devendra S.
Abstract: In the presented work, researchers used Efficiency defect as a parameter for deciding the utility of refrigerants in the Cascade refrigeration system. Cascade refrigeration system's mathematical model is created. Using the first and the second law of thermodynamics energy analysis and exergy analysis are done for different low Global warming potential refrigerant pairs like R134a/CO2, R1234yf/CO2, and R1234ze/CO2 . Based on the analysis efficiency defect is calculated for every component of the cascade system individually and the whole system as well. It is found that R1234yf/CO2 has the highest value of efficiency defect, whereas R134a/CO2 has the least efficiency defect for the whole cascade system. Change of efficiency defect in various components with evaporator temperature is presented in form of graphs.